2003
DOI: 10.1081/al-120023613
|View full text |Cite
|
Sign up to set email alerts
|

Indophenol andO-Quinone Derivatives Immobilized on Zirconium Phosphate for NADH Electro-oxidation

Abstract: The electrocatalytic properties for NADH oxidation of five organic dyes, two indophenol derivatives (2,6-dichlorophenolindophenol and indophenol) and three o-quinone derivatives (phenanthrenequinone, pyrroloquinoline-quinone, and 1,2-naphthoquinone) were compared when adsorbed on zirconium phosphate entrapped in carbon paste. The electrochemical behavior of the immobilized dyes was investigated with cyclic voltammetry, performed in different aqueous MARCEL DEKKER, INC. • 270 MADISON AVENUE • NEW YORK, NY 10016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
4
22
2
Order By: Relevance
“…Several authors have demonstrated the use of this material for the construction of NADH biosensors. Mediators previously immobilized in α-ZrP are phenoxazines, phenothiazines, phenazines, fluorenones and flavines [15,[37][38][39][40]. These authors did not use enzymes in their studies nor provided X-ray powder diffraction (XRPD) evidence of the mediator intercalation into the layered material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have demonstrated the use of this material for the construction of NADH biosensors. Mediators previously immobilized in α-ZrP are phenoxazines, phenothiazines, phenazines, fluorenones and flavines [15,[37][38][39][40]. These authors did not use enzymes in their studies nor provided X-ray powder diffraction (XRPD) evidence of the mediator intercalation into the layered material.…”
Section: Introductionmentioning
confidence: 99%
“…However, the electrochemical oxidation of NADH (or NADPH) requires a high overvoltage and suffers from side chemical reactions [18,19]. The use of redox mediators has been demonstrated to substantially overcome these limitations, particularly in dehydrogenase sensors [4,15,20]. Ideal mediators should exhibit chemical and electrochemical reversibility, stability under physiological conditions, a fast electron exchange reaction with the coenzymes, and a suitable redox potential, usually between −0.2 to 0 V vs. SCE to avoid interferences in biological determinations [5,18,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have demonstrated the use of α-zirconium phosphate for the construction of NADH biosensors. Mediators that have been immobilized in α-zirconium phosphate are Nile blue (Malinauskas et al 2000), toluidine blue (Malinauskas et al 2000), Meldola's Blue (Ladiu et al 2007;Munteanu et al 2001), methylene green (Munteanu et al 2001), 2,4,7-trinitro-9-fluorenone (Munteanu et al 2002), and 2,6-dichlorophenolindophenol (Dicu et al 2003). Cyclic voltammetric investigations of Meldola's Blue, methylene green, and riboflavin immobilized on α-zirconium phosphate performed in buffered solutions at different pHs have also been performed (Munteanu et al 2001).…”
Section: )mentioning
confidence: 99%
“…Furthermore, for a catalytic system, the pH independency is helpful due to different pH optima of the enzymes and limited buffer capacity of the solution. The addition of Ca 2+ to a buffered solution of 2,6-dichlorophenolindophenol adsorbed on α-zirconium phosphate in the presence of NADH was shown to increase the oxidation current (Dicu et al 2003). The kinetic parameters obtained for Meldola's Blue adsorbed via zirconium phosphate on a GC paste electrode were adversely influenced by increased surface coverage (Γ) (Ladiu et al 2007).…”
Section: )mentioning
confidence: 99%